KEGIATAN FARMAKOLOGIS DARI BERBAGAI BAGIAN Carica papaya Linn. EKSTRAK: BUAH, DAUN, BENIH, UAP, KULIT DAN AKAR - Hidayati, Tita Kosima; Susilawati, Yasmiwar; Muhtadi, Ahmad (Jurnal Riset Kefarmasian Indonesia, 2020)
Carica papaya (Caricaceae) Linn. (CP) is a popular tropical plant which provide a huge benefit. The fruit is either delicious and healthy while other parts have a great potential medicinal properties. CP are classified as plants that have anti-microbial activity, anti oxidant, anti malaria, anti-ulcer, anti-HIV, anti-inflammatory, anti-cancer, anti-hypertension, anti-fertility, anti-fungal and anti diabetic. Pharmacological activity of papaya plants related to the content of phytochemical compounds of alkaloid, flavonoid , tannin, saponin, enzyme: papain and chymopapain. These phytochemical content have been found in the young leaf, stem bark, dry seeds. Papaya leaf reveal more pharmacologycal activities because that have wide variety of phytochemical contents. In this review will be studied pharmacologycal activities of Carica papaya Linn. extract that obtained from fruit, leaf, seeds, stem bark and root. Besides, their various phytochemical contents are also described.